Revising WSDL documents: Why and How - Crasso, Marco Patricio (2010)
Although Web service technologies promote reuse, Web Services Description Language (WSDL) documents that are supposed to describe the API that services offer often fail to do so properly. Therefore, finding services, understanding what they do, and reusing them are challenging tasks. The authors describe the most common errors they’ve found in real WSDL documents, explain how these errors impact service discovery, and present some guidelines for revising them.